Acute effects of prior conditioning activity on change of direction performance. A systematic review and meta-analysis - Singh, U.; Connor, J. D.; Leicht, A. S.; Brice, S. M.; Doma, K. (Journal of Sports Sciences, 2023)
We performed a systematic review and meta-analysis on the acute effects of prior conditioning activity (CA) on change of direction (COD) performance. Eligible studies, involving healthy participants undergoing acute CA with at least one measure of COD performance, were analysed across diverse databases. A total of 34 studies were included for systematic review with 19 studies included for the meta-analysis. The intervention condition resulted in significantly faster (Z = 4.39; standard mean difference [SMD] = 0.49; p < 0.05) COD performance compared with the control condition. Both unloaded and light loaded CA resulted in significantly greater (SMD = 0.58-0.59) COD performance compared to the control condition. Moreover, heavy loaded CA demonstrated a significant but small (SMD = 0.24) improvement in COD performance compared to the control condition. Age and study design had no effect on the overall meta-analysis outcomes. Both males and females exhibited similar moderate effects with CA but only males demonstrated significantly greater COD performance compared to control conditions. Our findings indicate that a range of CA protocols can acutely improve COD performance with unloaded and light-loaded CA resulting in the greatest performance enhancements. These findings will assist practitioners with the design and implementation of appropriate acute CA to improve COD performance.